PENGEMBANGAN BUDIDAYA RUMPUT LAUT DI SUMBAWA BERBASIS TEORI TRIPLE HELIX - Bintang Rizki Sakinah (Jurnal Ilmiah Wahana Bhakti Praja, 2017)
Indonesia is a unitary state consisting of clusters of large and small islands connected by wide oceans and has the potential to support the development of local and national economies to increase foreign exchange earnings, employment, and incomes of the population. One area in Indonesia that utilize the results of the sea is Sumbawa regency of West Nusa Tenggara. Based on the Decree of the Minister of Marine Affairs and Fisheries No. KEP.32 / MEN / 2010 on Establishment of Regions Minapolitan as amended by Decree of the Minister of Marine Affairs and Fisheries No. KEP.39 / MEN / 2011, Sumbawa as the one Minapolitan of 179 Minapolitan in Indonesia by commodities seaweed seed. Minapolitan is the conception of economic development of region-based marine and fisheries based on the principles of integration, efficiency, quality and speed. There are 6 sub-district as a point of land development seaweed in Sumbawa, one of which is the village of Labuhan kuris District of Lape with seaweed production reached 29.436 tonnes with utilization area growing as many as 1328.51 hectares. Given these commodities, Sumbawa opportunity to step forward does not seem difficult. However, the potential of it did not make the state of the local community shifted from the poverty line. To overcome this, the need for conductor linking between education, technology, and labor market through the application of the theory of the Triple Helix. The main thinking triple helix theory is the importance of synergy between academic, business, and government. This paper intends to elaborate on the opportunities and challenges minapolitan as a form of education and technology alignment and an application of the theory of the triple helix in improving community development and regional competitiveness. The results of this research that needed collaborate academic, business and government to seaweed cultivation development and make empowerment and welfare local community.Keywords: Empowerment, Minapolitan, Triple Helix, Education, Technology